Manajemen Strategik Pengembangan Budaya Akademik Perguruan Tinggi Keagamaan Islam Negeri di Era Digital - Dina, Sarah; Phangesti, Dwinanda Suluh; Hafizh, Muhammad (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
The digital era produces people's lives that are more practical. As a result, not a few academic communities choose a new culture that is identical more instantly than the old culture. The development of a good academic culture is closely related to the role and function of effective education management because this is a reference for improving the quality of the educational process. This study aims to explore how management plans the development strategy of PTKIN's academic culture in the digitalization era. The research method applied is a qualitative method with a type of literature review (literature review). The technical data analysis is to use data reduction, data presentation, and drawing conclusions. The results of this study were found. First, one of the reasons for the decline of PTKIN's academic culture in the digitalization era is the ineffective management of education. As a result, various facts indicate a lot of negative news about violations of academic cultures, such as; 1) rampant cases of plagiarism in tertiary institutions, 2) lack of a culture of reading, discussion, and research among students, 3) sexual harassment by unscrupulous university officials, and even 4) forgery of diplomas and even buying and selling of degrees. Second, in order to overcome the degradation of academic culture in tertiary institutions, several steps are needed: 1) good management involving several authorized parties, 2) implementing higher education autonomy effectively, and 3) utilizing resources that understand information technology within the PTKIN environment.